A case of superior mesenteric artery syndrome got physicians in trouble. Issue 1 (31st January 2021) - Badour, Maysaa; Mahmoud, Gaber; Hasan, Ahmad; Sulaiman, Walaa; Hammed, Ali
Abstract: Superior mesenteric artery (SMA) syndrome is a gastrovascular disorder in which the third and final portion of the duodenum is compressed between the abdominal aorta (AA) and the overlying SMA. Our case presents an 11-year-old female with chronic intermittent vomiting that started since she was 6 months old. Contrast enhanced computed tomography scan for abdomen and pelvis guided to the correct diagnosis and the patient received the adequate treatment. Awareness of a broad range of differential diagnosis of vomiting and a high degree of suspicion of SMA syndrome is fundamental in order to direct the proper diagnostic investigation. Duodenojejunostomy provides the best results in severe cases.